Dynamic of Arabica Coffee Marketing Organization in Ngada District:Progress upon Implementing of Geographical Indication - Lya Aklimawati (Indonesian Coffee and Cocoa Research Institute, 2017)
Farmer organization has important role on coffee agribusiness development. Organization was positioned as a driving force on farmer economic activities, especially in strengthening partnership networks. Realizing the importance of organization, the aim of this research was to identify the coffee market structure in the scheme of Geographical Indication; to analyze the dynamic of coffee marketing organization at farmers level; and to analyze added value of wet parchment bean sales at the farmers organization. This research was conducted in Ngada District which includes Bajawa, Golewa and West Golewa Sub-district. Respondents in this study were 100 farmers which determined by using simple random samplingmethod. The primary data was based on questionnaire and secondary data was from journals, articles, and internal reports. Data were analyzed with descriptivequalitativeapproach and Hayami method. The results showed that coffee market structure in Ngada District lead to imperfect competition market (monopsonyoligopsony). The dynamic of farmers organization worked in progress which shown through ease access to market information and networking. Vertically organizational relationship between farmers and other market cooperatives has been established. Added value at UPHs/cooperative in the coffee supply chain was 15,35% of output value